1980
DOI: 10.1029/jc085ic08p04468
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and concentrations of hydrogen sulfide in the air of the tropical forest of the Ivory Coast and of temperate regions in France

Abstract: Atmospheric H2S was measured by a fluorometric method (sensitivity 10 rig). In France, for aerated soils the emissions were between 0.8 and 27/•g m -2 h -t H2S (average 5/•g m -2 h-•). The soil temperature is an important factor governing this emission. The H2S concentrations in the air ranged from 0.017 to 0.17 gg m -3 (average 0.080/•g m-3). In the Ivory Coast the H•S emissions were estimated between 30 and 300 p.g m -• h -t. The measured concentrations of H2S in the air at ground level ranged from 0.10 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Measurements of fluxes of volatile sulfur compounds from various surfaces were made using an emission flux chamber similar to those used by Hansen et aL, 1978;Delmas et al, 1980;Adams et aL, 1981;Carroll, 1983;Hill et al, 1978;and Steudler and Peterson, 1984. This technique involves the placement of an open-bottomed enclosure over an area of soil, mud, or water, either including or excluding vegetation as desired, and passing through the enclosure a sweep gas that is usually, but not necessarily, free of the species of interest.…”
Section: Equipmentmentioning
confidence: 99%
“…Measurements of fluxes of volatile sulfur compounds from various surfaces were made using an emission flux chamber similar to those used by Hansen et aL, 1978;Delmas et al, 1980;Adams et aL, 1981;Carroll, 1983;Hill et al, 1978;and Steudler and Peterson, 1984. This technique involves the placement of an open-bottomed enclosure over an area of soil, mud, or water, either including or excluding vegetation as desired, and passing through the enclosure a sweep gas that is usually, but not necessarily, free of the species of interest.…”
Section: Equipmentmentioning
confidence: 99%
“…At present, no determination of the emission of S compounds have been made in Venezuela. Delmas et al (1980) reported an average emission of 1.27 × 10 -7 g H2S-S m -2 s -1 for the savannah region of the Ivory Coast. Considering that a significant fraction of the Venezuelan savannah becomes flooded, a similar or even larger sulphur emission from the soils could be expected during the rainy season.…”
Section: Rainy Seasonmentioning
confidence: 99%
“…Fluxes between 0.001 and 1.1 g S m~2 yr" 1 were reported from marshland soils in the Enis River region of northern Germany. 17 However mean annual fluxes from tropical soils in the Ivory Coast 37 are much higher than those in the U.S. and European soils, ranging between 0.3 to 0.9 g S m~2 yr" 1 . Several recent studies have reported additional data from the earlier U.S. site for the emission rates of biogenic The newer data by Lamb et al 29 and Goldan et al 28 seem to suggest that the sulfur flux appears to have decreased 70 from measurements made earlier.…”
Section: Biogenic Emissions From Landmentioning
confidence: 99%